A limit state design approach for hybrid reinforced concrete column‐supported flat slabs. (18th March 2022) - Aidarov, Stanislav; Tošić, Nikola; de la Fuente, Albert
Abstract: Hybrid reinforced technology (combination of steel reinforcing bars and fibers) can be considered as a competitive alternative to the already existing solutions for the construction of column‐supported flat slabs. Constructed hybrid‐reinforced buildings prove that hybrid solutions have sufficient bearing capacity to maintain structural integrity despite being exposed to high stress levels, thereby providing a beneficial solution in terms of toughness, ductility, and sustainability performance. However, the lack of design‐oriented recommendations based on the accepted limit state format for dealing with both serviceability and ultimate limit states slows down the wider implementation of this technology. Considering the above‐mentioned, this article presents a simplified design‐oriented method that covers the evaluation of the structural response of hybrid reinforced concrete column‐supported flat slabs in terms of flexural strength, cracking, and instantaneous deformations. Two hybrid reinforced alternatives for a given flat slab are studied by means of the proposed approach. Furthermore, a nonlinear finite element analysis is carried out in order to evaluate the effectiveness of the developed simplified method. Based on the achieved results, its suitable accuracy and precision can be pointed out. This outcome may motivate current practitioners to consider hybrid reinforced concrete solutions as a possible alternative during the design of residential and office buildings.